Reconciling Aboriginal and White Australians by Negotiating Spatial Boundaries in The Secret River:: A Postmemory Study - Sri Sumaryani; Zuhrul Anam (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2022)
The dichotomic concept of space between white and Aboriginal Australians has been widely used in the colonial discourse. Through The Secret River, Grenville dismantles the binary oppositions that serves as the main strategy for colonization. We argue that space as a medium of negotiation is used as her strategy to involve in the national reconciliation movement. Postmemory is employed to explain the strategy of choosing spatial locations that links with Grenville’s intergenerational memories. The analysis reveals that the boundaries created by the settlers upon the disputed land cannot successfully cover the chaotic and heterogenous nature of the Aboriginal Dharug land. Instead, the previous characteristics of the land keep appearing as a form of resistance. During the attempt, the settlers slowly recognize the similar nature of the Dharug’s living space to theirs. The process represents the ongoing understanding between the two parties which signifies the spirit of the national reconciliation movement.